An Examination of the Interaction Effects of Hospitality Employees' Motivational and Cultural Factors in the Workplace. Issue 3 (27th May 2022) - Zheng, Tony Minghao; Zhu, Dan; Kim, Peter Beomcheol; Williamson, David
ABSTRACT: This study examines the unique effects of hospitality employees' perceptions of two types of motivation factors (intrinsic and extrinsic-hygiene) on their turnover intention and service-oriented organizational citizenship behavior (SOCB). Further, the study investigates the moderating role of power distance on the impacts of these two types of employee motivation factors. A series of hierarchical multiple regression analyses were performed to test the research hypotheses using the responses to a structured survey of 203 hospitality employees in New Zealand. The findings demonstrate that hospitality employees' perception of extrinsic-hygiene motivation factors has a stronger influence on their turnover intention while their perception of intrinsic motivation factors has a more salient impact on the exhibition of SOCB. The moderating role of power distance was found in the effect of hygiene factors on turnover intention (stronger in low power distance), that of intrinsic factors on turnover intention (stronger in low power distance), and that of intrinsic factors on SOCB (stronger in high power distance). The implications of the findings for researchers and practitioners and recommendations for future research are elucidated.